KORELASI ANTARA DUKUNGAN KELUARGA DENGAN TINGKAT DEPRESI PASIEN HUMAN IMMUNODEFFICIENCY VIRUS (HIV) POSITIF RUMAH SAKIT X DI KABUPATEN BANYUMAS - Luqlun Salisa Sugiarto; Hilma Paramita; Diyah Woro Dwi Lestari (Fakultas Kedokteran Universitas Jenderal Soedirman, 2021)
HIV is a chronic infectious disease that can affect mental and psychological patients. This disease causes psychiatric problems, for example depression. Depression can affect the quality of life and motivation of patients. To overcome this, good social support from the patient's family is needed. The purposes of this study were to determine the correlation between family support and depression levels in positive HIV patients at “X” Hospital in Banyumas Regency. This study used observational analytic with cross sectional approach. Primary data were collected from questionnaires and medical records from 23 positive HIV patients at “X” Hospital in Banyumas Regency who met the inclusion criteria. The sample datas were collected using consecutive sampling technique by taking the L-MMPI questionnaire data, the BDI-II questionnaire for depression levels, and the Friedman family support questionnaire. Afterwards, hypothesis analysis was done using the Spearman test. Data showed that most respondents had good family support and 1/3 respondents did not experience depression or normal. The correlation between family support and depression level was processed using the Spearman rho correlation test with a significance level of p ≤ 0.05. The test results (p = 0.002) showed that there was a significant correlation between family support and the depression level of positive HIV patients at “X” Hospital in Banyumas Regency. From this study can be concluded that the respondents with good family support did not experience symptoms of depression or normal. Family support is needed to prevent depression in positive HIV patient.